2009
DOI: 10.1099/mic.0.027714-0
|View full text |Cite
|
Sign up to set email alerts
|

ACCase 6 is the essential acetyl-CoA carboxylase involved in fatty acid and mycolic acid biosynthesis in mycobacteria

Abstract: Mycolic acids are essential for the survival, virulence and antibiotic resistance of the human pathogen Mycobacterium tuberculosis. Inhibitors of mycolic acid biosynthesis, such as isoniazid and ethionamide, have been used as efficient drugs for the treatment of tuberculosis. However, the increase in cases of multidrug-resistant tuberculosis has prompted a search for new targets and agents that could also affect synthesis of mycolic acids. In mycobacteria, the acyl-CoA carboxylases (ACCases) provide the buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
0
47
2
Order By: Relevance
“…Using this technique, we provided compelling evidence that accD6 is indeed an essential gene in M. tuberculosis under the culture conditions described, thereby confirming the previous predictive data. However, in contrast to the previous report by Kurth et al (36), we were able to remove the functional accD6 gene from the chromosome of M. smegmatis. Deletion of accD6 in M. smegmatis was performed in two independent experiments and was confirmed by all typical techniques, as described in Results.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Using this technique, we provided compelling evidence that accD6 is indeed an essential gene in M. tuberculosis under the culture conditions described, thereby confirming the previous predictive data. However, in contrast to the previous report by Kurth et al (36), we were able to remove the functional accD6 gene from the chromosome of M. smegmatis. Deletion of accD6 in M. smegmatis was performed in two independent experiments and was confirmed by all typical techniques, as described in Results.…”
Section: Discussioncontrasting
confidence: 54%
“…However, due to the essential nature of accD6, the possible involvement of AccD6 in mycolic acid biosynthesis has never been addressed in vivo. Until now, only one study concerning the probable function of accD6 in the fast-growing nonpathogenic species Mycobacterium smegmatis has been conducted (36).…”
mentioning
confidence: 99%
“…Mammalian cells acquire biotin from the external environment and thus lack these enzymes, therefore validating this pathway for developing intrinsically selective anti-TB drugs. 117 Furthermore, mutants in the biotin synthesis pathway can cause only attenuated forms of infections in mice, suggesting the pathogen is unable to obtain exogenous biotin. 118 Prof Schnappinger and his group found that mutating one of the enzymes, BioA (biotin ligase) in M. tuberculosis made it incapable of surviving in vitro and in mice indicating that the de novo biotin synthesis is critical for the pathogen's survival and persistence.…”
Section: The Search For Novel Therapeutic Targetsmentioning
confidence: 99%
“…It catalyzes the ATP dependent carboxylation of Acetyl CoA to form malonyl CoA, which is the precursor of fatty acids (Sellwood et al, 2000). It is present in prokaryotes, chloroplasts of most plants and algae, endoplasmic reticulum of most eukariotes, and even mycobacteria (Kurth et al, 2009). ACCase catalyses two partial reaction occurring at two different sites (Fig.…”
Section: Acetyle Coa Carboxylase (Accase)mentioning
confidence: 99%